18F-FDG PET/CT Uptake in Acute Pontine Infarct Mimicking Intracranial Metastasis. (20th September 2022) - SathyaMurthi, Banu; Muthu, Sivakumar; Howard, James; Sajjan, Rakesh
Abstract: Infarcts are generally nonviable and are not avid on an 18 F-FDG PET/CT. Here, we discuss a 53-year-old man who presented with chest pain and raised d -dimer. CT pulmonary angiogram was performed to exclude pulmonary embolism, which identified incidental lung nodules. 18 F-FDG PET/CT was performed for the assessment of lung nodules, which showed incidental focal FDG uptake in the pons. This was concluded as an acute infarct on subsequent MR scan. This highlights the importance of not interpreting all focal FDG uptakes as malignant. In rare circumstances, false-positive benign causes should be considered, such as in this rare case of an acute pontine infarct.